Reverse zoonosis of SARS-CoV-2: literature review - Cymer, Emil; Adamczyk-Popławska, Monika; Kubuj-Pawliszyn, Malwina; Anasiewicz, Michał; Wójcik, Bartłomiej; Zagajewska, Maria; Borodacz, Julia; Czampiel, Martyna; Dryżałowski, Piotr (Journal of Education, Health and Sport, 2026)
Introduction: SARS-CoV-2, the causative agent of COVID-19, was initially considered primarily a pathogen transmitted between humans. As the pandemic unfolded, attention turned to the phenomenon of reverse zoonosis—that is, the transmission of the virus from humans to animals—which may have significant epidemiological and environmental implications. Objective: The aim of this study was to analyze available data on SARS-CoV-2 reverse zoonosis, with particular emphasis on the susceptibility of various animal species, mechanisms of infection, and potential public health implications. Materials and methods: An analysis was conducted of the scientific literature cited in the study, encompassing experimental and observational studies as well as clinical reports. The analysis included results from molecular (RT-PCR) and serological tests, phylogenetic analyses, and data on ACE2 receptor homology across various animal species. Results: It was demonstrated that SARS-CoV-2 can infect numerous animal species, including domestic, farmed, and wild animals. The highest susceptibility is observed in felids, minks, and ferrets. In many cases, transmission of the virus from humans to animals has been confirmed, and sporadically also between animals and from animals to humans. The course of infection is most often asymptomatic or mild, although severe complications are possible. Conclusions: Reverse zoonosis of SARS-CoV-2 is a significant issue that requires further research and monitoring. Animals may serve as reservoirs for the virus and sources of new variants. It is essential to implement biosecurity measures and foster interdisciplinary collaboration to minimize the risk of interspecies transmission.